The effectiveness of WhatsApp video to increase knowledge of pneumonia early detection among mothers of children under five years - Ni Wayan Erviana Puspita Dewi; Anak Agung Sagung Sawitri; Partha Muliawan (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Number of people in Indonesia who have access to smartphones is quite high, but their use for health education media specifically for the detection of pneumonia is still limited. This study aims to determine the effectiveness of use of video information through the WhatsApp (WA) application compared to leaflets in order to increase maternal knowledge about early detection of pneumonia among under-five children. Methods: A pretest-posttest randomized control trial was conducted in three of the six sub-villages (called banjar) in the Gelgel Village, Klungkung District. Banjar was selected purposively by considering the distance between banjar. As many as 30 mothers were selected as samples from around 45-50 mothers of children under five in each banjar. The intervention was conducted randomly where one banjar was given intervention with videos through WA, one banjar with leaflets and one banjar as a control group. The intervention was carried out for three weeks (August-September, 2018). Data were collected before and after the intervention through face-to-face interviews with the mothers in their homes, which included social demographics, mother's knowledge about pneumonia detection and educational media preferences. Bivariate data analysis was conducted with paired t-test and multivariate analysis with General Linear Model. Results: Characteristics of respondents in all three groups were similar in terms of age, education, employment, and parity. The results of interviews on educational media choices showed that most respondents (64%) preferred WA media. The increase in mean knowledge score after the intervention was significantly higher in the WA group which was 6.93 (95%CI: 6.38-7.49) and leaflet 5.90 (95%CI: 5.49-6.44) compared to the control group 1.87 (95%CI: 1.26-2.47). There was no significant difference between the WA and the leaflet group. The results of multivariate analysis showed that educational media (F=110.99; p<0.01) and education (F=16.69; p<0.01) were significantly associated with the increase in knowledge after adjustments were made based on age, employment and parity. Conclusion: WA videos and leaflet were found to be effective in increasing maternal knowledge about early detection of pneumonia in under-five children. Because the use of WA application is increasing, efforts to improve health knowledge with WA videos need to be enhanced.